Biodiesel preparation from microalgae lipid by two-step lipase catalysis. Issue 5 (3rd September 2017) - Gong, Guiping; Meisi, Linshuo; Zhang, Xu; Tan, Tianwei
Abstract: To overcome the high energy-consuming process of microalgae drying, a two-step lipase catalysis technique for the preparation of biodiesel from microalgae lipid of Chlorella spp . was developed. In the first step, free fatty acids (FAAs) and triacylglycerols (TAGs) are released after cell disruption and extracted, while the TAGs were hydrolysed by free lipase in aqueous phase. In the second step, FAAs were esterified with ethanol in the catalysis of free suspended lipase. The maximum rate of hydrolysis and esterification was 93.6% and 91.3%, respectively. The effects of reaction parameters, such as reaction time, enzyme amount, water content and molar ratio of lipid to ethanol on hydrolysis or esterification, were investigated. The results indicated that two-step reaction process (hydrolyse esterify) for biodiesel production were feasible.